A glance on the role of fibronectin in controlling cell response at biomaterial interface - Ludovica Parisi; Andrea Toffoli; Benedetta Ghezzi; Beatrice Mozzoni; Simone Lumetti; Guido M. Macaluso (Elsevier, 2020)
Summary: The bioactivity of biomaterials is closely related to cell response in contact with them. However, shortly after their insertion, materials are soon covered with proteins that constitute the biological fluids, and which render the direct surface recognition by cells almost impossible. The control of protein adsorption at the interface is therefore desirable. Extracellular matrix proteins are of particular interest in this sense, due to their well-known ability to modulate cell behavior. Particularly, fibronectin plays a leading role, being present in both healthy and injured tissues undergoing healing and regeneration. The aim of the present work is to give an overview on fibronectin and on its involvement in the control of cell behavior providing evidence of its pivotal role in the control of cell adhesion, spreading, migration, proliferation and differentiation. A deep insight into methods to enrich biomaterials surface with fibronectin will be then discussed, as well as new cues on the possibility to design tailored platforms able to specifically retain fibronectin from the surrounding extracellular milieu.